Faktor-faktor yang Memengaruhi Persepsi Wakif terhadap Wakaf Uang di Kota Bogor - Syifa Fauziah; Salahuddin El Ayyubi (Department of Islamic Economics, IPB University, 2019)
Waqf has a potential in developing a social and economic aspect of society. The development of waqf instrument in the attempt of social and economic growth is able to be obtained through the new concept of waqf, that is cash waqf. However, the realization of cash waqf collection was not met its potential. Based on the previous studies, one of the factors that caused the low quantity of cash waqf collection was the people that had less awareness and comprehension towards cash waqf. Even several people that already gave their waqf had only known the waqf in the form of immovable asset. This study aims to describe respondents’ characteristics and analyze the possible factors that affect wakifs’ perception towards cash waqf in Bogor City. The method used in this study was descriptive analysis and logistic regression analysis. This study was done in Bogor City and involved 50 respondents. Based on the data analysis results, wakifs’ perception was known to be affected by their comprehension towards cash waqf and their social motivation.